The incomplete revolution. Adapting welfare states to women's new roles - Esping-Andersen, Gøsta (Chichester, 2009)
"Our future depends very much on how we respond to three great challenges of the new century, all of which threaten to increase social inequality: first, how we adapt institutions to the new role of women - the ‘incomplete revolution' of our time; second, how we prepare our children for the knowledge economy; and, third, how we respond to the new demography, in particular low fertility and an ageing population.